Classical Music Criticism at the Globe and Mail: 1936-2000 - Eatock, Colin (Canadian University Music Review / Revue de musique des universités canadiennes, 2004)
This article is a study of developments in classical music criticism at the Toronto-based Globe and Mail newspaper from its inception in 1936 to the year 2000. Three distinct time-periods are identified, according to content, style and ideology: 1936-1952, a period of boosterism, when critics often saw it as their role to support Toronto's musicians and musical institutions; 1952-1987, when (during the lengthy tenure of critic John Kraglund) the newspaper took a more detached, non-partisan stance towards musicians and musical activities in the city; and 1987-2000, when critics began to address social, political, and economic issues governing classical music, and to question inherited cultural assumptions about the art form.